(untitled) (Acta Polytechnica CTU Proceedings, 2022)
A preliminary study of two approaches for the internal structure generation utilized in the lattice discrete particle models (LDPM) [1] is presented. The presented methods used for particle generation and placement are meant to capture the internal structure of materials realistically. The first approach governs the positioning of the generated spherical particles by a gradient field to mimic the casting process. The second approach considers the non-spherical shape of individual particles, i.e. ellipsoidal particles. Therefore, the grain size, angularity, and flakiness can be controlled to match the real grain distribution closely.